Emerging technologies for profiling extracellular vesicle heterogeneity. Issue 14 (15th June 2020) - Huang, Guan; Lin, Gungun; Zhu, Ying; Duan, Wei; Jin, Dayong
Abstract : Approaches, challenges and promising opportunities towards decoding the complexity of extracellular vesicle heterogeneity are discussed. Abstract : Extracellular vesicles (EVs) are membrane-bound vesicles secreted by most cell types and exist in virtually all bodily fluids. They carry on a wealth of proteomic and genetic information including proteins, lipids, miRNAs, mRNA, non-coding RNA and other molecules from parental cells. Increasing evidence shows that within populations of EVs, their biogenesis, physical characteristics ( e.g. size, density, morphology) and cargos ( e.g. protein, lipid content, nucleic acids) may vary substantially, which accordingly change their biological properties. To fully exploit the potential of EVs, it requires qualified methods to profile EV heterogeneity. In this review, we survey recent approaches for EV isolation with innovative discoveries in heterogeneity. The main challenges in EV heterogeneity research are identified, and the roles of single cell EV profiling and single EV imaging are highlighted. We further discuss promising opportunities for resolving the underlying complexity of EV heterogeneity.